ANALISIS TEKNIK SMASH SEBAGAI FAKTOR PENENTU KEBERHASILAN SERANGAN DALAM PERMAINAN BULUTANGKIS - Icha Amelia Putri; Cindy Rasika Amalia; Latipa Harahap (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Smash is one of the most important attacking techniques in badminton because it is often used to pressure the opponent and create opportunities to score points. However, the success of a smash is not only determined by hitting power, but also by technical accuracy, body coordination, timing, racket angle, shuttlecock placement, and the player’s ability to read game situations. This article aims to analyze smash technique as a determining factor in the success of attacks in badminton. This study uses a descriptive qualitative method with a literature review approach. Data were obtained from scientific journals, academic articles, and relevant open-access literature related to badminton smash technique, biomechanics, smash accuracy, and training methods. The results show that an effective smash requires a coordinated movement sequence, starting from preparation, racket swing, shuttlecock contact, and follow-through movement. In addition, accuracy and shot placement are important factors that determine whether a smash can pressure the opponent effectively. Therefore, smash technique can be considered an important factor in the success of attacking play in badminton, although it still needs to be supported by physical condition, tactical awareness, and consistent training.